THE RIGHTS AND OBLIGATIONS OF THE STATE IN THE RESTORATION OF CULTURAL HERITAGE: A REVIEW ON INTERNATIONAL LAW AND THE PRACTICE OF INDONESIA - Adinugraha, Antonius Satria (Indonesian Journal of International Law, 2016)
This article will focus on Indonesia’s effort based on international law to restore its cultural heritage. The problem about cultural heritage retention in international law is always related to two conflicting interests. On one hand, there are many developed states that try to keep abundant cultural heritages from all over the world. On the other hand, there are developing states that try to protect and even restore their cultural heritage during post-independence period. Indonesia is one of developing states that possess abundant cultural heritage. Unfortunately, Indonesia has not been able to fully maximize its right of restoration that is recognized in international law.